Isolation and characterization of antimicrobial producing bacteria from part of plant (piper nigrum) against phytophthora capsici - Nur Atikha Shasha, Binti Azhar (Universiti Malaysia Sarawak, UNIMAS, 2013)
Piper nigrum, or black pepper, is in the family Piperaceae and in the kingdom of Plantae. The cultivation used the fruit to produce spice. Among the major diseases of pepper are Phytophthora foot rot caused by Phytophthora capsici. The aim of this study is to screen for the antimicrobial producing bacteria that can inhibit the Phytophthora sp. These bacteria will be used to control plant disease caused by P. capsici. The samples were taken from “Kebun Lada Kampung Raeh” and “Kebun Lada Contoh Kampung Daha Kisau” under Malaysia Pepper Board (MPB). In this study, five parts of P. nigrum were taken which are root, shoot, stem, leaf and berry and the bacteria that inhibit the Phytophthora sp. were subjected to primary and secondary screening through Agar-Well Diffusion and Spot Inoculation Method. Then, bacteria that shown inhibition activity against Phytophthora sp. were isolated, identified and characterized by using PCR analysis. The bacteria that can inhibit P. capsici were identified as Delftia tsuruhatensis and Bacillus pumilus. These bacteria may help in control of the disease in pepper by inhibiting the growth of P. capsici.